2020
DOI: 10.3390/jfb11030056
|View full text |Cite
|
Sign up to set email alerts
|

Novel CaF2 Nanocomposites with Antibacterial Function and Fluoride and Calcium Ion Release to Inhibit Oral Biofilm and Protect Teeth

Abstract: (1) Background: The objective of this study was to develop a novel dental nanocomposite containing dimethylaminohexadecyl methacrylate (DMAHDM), 2-methacryloyloxyethyl phosphorylcholine (MPC), and nanoparticles of calcium fluoride (nCaF2) for preventing recurrent caries via antibacterial, protein repellent and fluoride releasing capabilities. (2) Methods: Composites were made by adding 3% MPC, 3% DMAHDM and 15% nCaF2 into bisphenol A glycidyl dimethacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 61 publications
1
51
0
Order By: Relevance
“…For example, medical devices with protein-repelling properties have been used in artificial blood vessels, implantable artificial hearts, and artificial lungs [ 28 ]. In dentistry, protein repellents have been synthesized with various chemical formulations and incorporated into composite materials, bonding agents, and denture acrylics to inhibit oral biofilm infections [ 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, medical devices with protein-repelling properties have been used in artificial blood vessels, implantable artificial hearts, and artificial lungs [ 28 ]. In dentistry, protein repellents have been synthesized with various chemical formulations and incorporated into composite materials, bonding agents, and denture acrylics to inhibit oral biofilm infections [ 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and fluoride are considered essential ions that can remineralize tooth structure [ 58 ]. The inclusion of CaF 2 nanoparticles in the material makes it antibacterial [ 59 ], stimulates fluoride release [ 60 ], and protects tooth structure against acidic attacks [ 61 ]. Historically, CaF 2 nanoparticles have been added in different dental materials, including pit and fissure sealants [ 62 ], glass ionomer cements [ 63 ], and DAs [ 64 ] and have yielded positive results.…”
Section: Bioactive Inorganic Fillersmentioning
confidence: 99%
“…Another earlier study reported that a 2.0 wt.% CaF 2 filler containing composite demonstrated the highest Vickers hardness, compared with the controls [ 67 ]. In a previous study, nanocomposites containing CaF 2 revealed strong antibacterial and ion releasing properties [ 61 ]. A significant concern with the use of CaF 2 nanoparticles is their stability; however, they are aptly stable in the oral environment than generally presumed [ 68 ].…”
Section: Bioactive Inorganic Fillersmentioning
confidence: 99%
“…However, it was not possible to maintain the ion releasing effect over a longer period of time [ 14 , 15 ]. Promising results were obtained with incorporation of nanoparticles of calcium fluoride (nCaF 2 ) to the nanocomposite filling material [ 16 ]. Another efficient source of fluoride ions used in the modification of dental materials are glasses or ceramics, which are a part of glass-ionomer cements (GIC): Full pre-reacted glass–ionomer fillers (F-PRG) and surface pre-reacted glass-ionomer cements (S-PRG) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%